2014
DOI: 10.1128/aem.03495-13
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Stabilizing mRNAs Involved in Methanol-Dependent Methanogenesis of Cold-Adaptive Methanosarcina mazei zm-15

Abstract: Methylotrophic methanogenesis predominates at low temperatures in the cold Zoige wetland in Tibet. To elucidate the basis of cold-adapted methanogenesis in these habitats, Methanosarcina mazei zm-15 was isolated, and the molecular basis of its cold activity was studied. For this strain, aceticlastic methanogenesis was reduced 7.7-fold during growth at 15°C versus 30°C. Methanol-derived methanogenesis decreased only 3-fold under the same conditions, suggesting that it is more cold adaptive. Reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…The similarity of mRNA degradation rates among related species grown under similar conditions—as evidenced by comparison of our results to the limited studies on M. mazei [66] and findings of other studies in other organisms [12, 14]—suggests that metabolic control points and regulatory modes identified in one organism could be inferred in the metabolism of similar organisms. From an evolutionary stand-point related organisms subjected to similar environments would likely retain regulatory controls that optimize their fitness.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The similarity of mRNA degradation rates among related species grown under similar conditions—as evidenced by comparison of our results to the limited studies on M. mazei [66] and findings of other studies in other organisms [12, 14]—suggests that metabolic control points and regulatory modes identified in one organism could be inferred in the metabolism of similar organisms. From an evolutionary stand-point related organisms subjected to similar environments would likely retain regulatory controls that optimize their fitness.…”
Section: Discussionsupporting
confidence: 81%
“…6 b and Additional file 1: Figure S13 and Additional file 3). Transcript counts also matched those measured in M. mazei [66] suggesting these Methanosarcina species could have similar transcription and degradation characteristics, similarly to the two Sulfolobus species. In general some of the conclusions drawn from this study might hold for evolutionarily related methanogens (e.g.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This unique architecture of the cspA mRNA allows it to function as a RNA thermometer9. Our recent work demonstrated that the mRNAs for mtaA and mtaC , which encode the methylcobalamin:coenzyme M methyltransferase and methanol corrinoid proteins that are the key enzymes in methanol-derived methanogenesis of a cold-adaptive methanogen, all have long 5′ UTRs, that contribute to the transcripts' stability at low temperatures10.…”
mentioning
confidence: 99%